Peningkatan Hasil Belajar Matematika Menggunakan Model Pembelajaran Problem Based Learning Dan Aplikasi Quizizz Di Kelas VII SMP Negeri 1 Kembang Janggut - Safitri, Riyanti Dewi; Safrudiannur, Safrudiannur; Azainil, Azainil (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2023)
This study aims to determine the improvement of mathematics learning outcomes using the Problem Based Learning model and Quizizz application in Class VII SMP Negeri 1 Kembang Janggut. The method is a class action research. The research subjects were VII-D class students as many as 28 students and the object of this research was the application of the Problem Based Learning model and Quizizz application. Data were obtained from observations, LKPD, exercises, assignments, and end-of-cycle tests. This research was conducted in three cycles. The data analysis technique is descriptive statistics in the form of the average value of learning outcomes. The results of data analysis showed an increase in the average value of student learning outcomes. The value of learning outcomes is obtained from observations, LKPD scores, exercises, assignments, and end-of-cycle tests. In cycle I, there is an increase from the basic value 47.64 to 64.77. In cycle II, it increased from the average 64.77 to 75.15. In cycle III, it increased from the average 75.15 to 86.01. The results of observations of teacher and student activities have also increased. In cycle I teacher activity was categorized as good and student activity was categorized as sufficient, in cycle II teacher activity was categorized as very good and student activity was categorized as good, and in cycle III teacher activity and student activity were categorized as very good.